Browning's experiments with genre - Hair, Donald S. ([Toronto] ; [Buffalo] : University of Toronto Press, 1972)
This book explores the kinds and modes with which Browning worked and describes the nature of the experiments he made, concentrating on the earlier poetry and in particular on The Ring and the Book.
Based on the author's thesis, University of Toronto.
Includes bibliographical references (pages 185-191).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Browning, Robert, -- 1812-1889 -- Technique; Browning, Robert -- Critique et interprétation.; Browning, Robert, -- 1812-1889; Browning, Robert -- 1812-1889; Browning, Robert; Literature, Experimental -- History and criticism; Literary form -- History -- 19th century; Poetics -- History -- 19th century; Littérature expérimentale -- Histoire et critique; Genres littéraires -- Histoire -- 19e siècle.; Poétique -- Histoire -- 19e siècle.; POETRY -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Literary form; Literature, Experimental; Poetics; Technique; 1800-1899; Criticism, interpretation, etc; History